Upaya Peningkatan Kedisiplinan Siswa Melalui Pembelajaran Pendidikan Agama Islam Pada Sekolah Menengah Pertama - Didit Karyanto (Universitas Muhammadiyah Sidoarjo, 2019)
Discipline is the attitude of the learner willingly to comply and do the rule in order to train themselves obey rules. Efforts to improve discipline starts from educators provide a good example when the learning process. Discipline is needed in learning, because it can help the learning process well, increasing the pleasure of students to learn, and help improve students' social relationships. The purpose of this study to reveal the efforts made through the learning of Islamic Education to improve the discipline of students in SMP HARAPAN Tulangan. This study includes qualitative study whose data in the form of statements, sentences, and documents. By using a naturalistic approach to researching where natural (natural setting) and field (Field Research), to obtain the required data information researchers used the method of observation, interviews, and documentation. Analysis of the data used in the form of triangulation analysis that includes data reduction, data presentation, and conclusion. From the research conducted by researchers showed: 1) The discipline of students of SMP HARAPAN has been good enough even though there are those who violate the rules. It still need to improve and reform the discipline of students so that they understand what is wrong even a little infractions. 2) The efforts of teacher to improve discipline students use the order. For example, when there is student break the rule of school, especially PAI’s teachers have to follow up violations that done by learners to give direction, punishment, or reward that is commensurate to what which is conducted.